Investigation of initial value dependence in the statistical analysis of ultrasonic scattered echoes for the non-invasive estimation of temperature distribution in biological tissue. (13th June 2019) - Takeuchi, Michio; Matsui, Yuta; Sakai, Toshihiko; Andocs, Gabor; Nagaoka, Ryo; Hasegawa, Hideyuki
Abstract: In the present study, the variation of the Nakagami shape parameter m of the probability distribution of amplitudes of ultrasonic echoes from soft tissue due to a temperature increase is shown to exhibit initial m -value dependence. The change of the Nakagami shape parameter m due to the temperature rise increased with increasing the initial m -value. In order to measure the temperature distribution in soft tissue, we propose a parameter that indicates the absolute values of ratio changes of m values with the multiplying factor varying as a function of the initial m -value. In the hot-scale images indicating the absolute values of ratio changes of m values with the consideration of the initial m -value dependence, the temperature distribution in soft tissue was visualized clearly.